2022
DOI: 10.1002/capr.12557
|View full text |Cite
|
Sign up to set email alerts
|

Recognition rates, treatment recommendations and stigma attributions for clients presenting with taboo intrusive thoughts: A vignette‐based survey of psychotherapists

Abstract: IntroductionObsessive compulsive disorder (OCD) is a prevalent mental health disorder which is characterised by high levels of morbidity. Most individuals with OCD do not receive adequate psychotherapeutic intervention. Research suggests that taboo intrusive thoughts are less likely to be recognised as OCD in comparison to more recognisable forms. Stigma attributions are higher for individuals with taboo intrusive thoughts. The aim of this study is to examine psychotherapists' capacity to recognise different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The behavior and attitude of mental health providers towards their clients can significantly affect treatment outcomes [42,43]. Nevertheless, the present study and the study by Canavan [27] provide encouraging data that show low levels of stigma among mental health professionals. This finding contrasts with several studies that have reported higher levels of stigma among mental health professionals.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…The behavior and attitude of mental health providers towards their clients can significantly affect treatment outcomes [42,43]. Nevertheless, the present study and the study by Canavan [27] provide encouraging data that show low levels of stigma among mental health professionals. This finding contrasts with several studies that have reported higher levels of stigma among mental health professionals.…”
Section: Discussionmentioning
confidence: 48%
“…With respect to client gender, there were no significant differences in recognition rates across any of the vignette subtypes. Consequently, the data for the male and female versions of each vignette type were combined for the remainder of the analysis, as reported by Canavan [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations